A simple phenotypic method for screening of MCR-1-mediated colistin resistance. (February 2018) - Coppi, M.; Cannatelli, A.; Antonelli, A.; Baccani, I.; Di Pilato, V.; Sennati, S.; Giani, T.; Rossolini, G.M.
Abstract: Objectives: To evaluate a novel method, the colistin-MAC test, for phenotypic screening of acquired colistin resistance mediated by transferable mcr-1 resistance determinants, based on colistin MIC reduction in the presence of dipicolinic acid (DPA). Methods: The colistin-MAC test consists in a broth microdilution method, in which colistin MIC is tested in the absence or presence of DPA (900 μg/mL). Overall, 74 colistin-resistant strains of Enterobacteriaceae (65 Escherichia coli and nine other species), including 61 strains carrying mcr-1 -like genes and 13 strains negative for mcr genes, were evaluated with the colistin-MAC test. The presence of mcr-1 -like and mcr-2 -like genes was assessed by real-time PCR and end-point PCR. For 20 strains, whole-genome sequencing data were also available. Results: A ≥8-fold reduction of colistin MIC in the presence of DPA was observed with 59 mcr-1 -positive strains, including 53 E. coli of clinical origin, three E. coli transconjugants carrying MCR-1-encoding plasmids, one Enterobacter cloacae complex and two Citrobacter spp. Colistin MICs were unchanged, increased or at most reduced by twofold with the 13 mcr- negative colistin-resistant strains (nine E. coli and four Klebsiella pneumoniae ), but also with two mcr-1- like - positive K. pneumoniae strains. Conclusions: The colistin-MAC test could be a simple phenotypic test for presumptive identification of mcr-1- positive strains among isolates of colistin-resistant E. coli, based on a ≥8-fold reduction of colistin MIC in the presence of DPA. Evaluation of the test with a larger number of strains, species and mcr -type resistance determinants would be of interest.